Phosphorus fertilization, yield and quality of seeds in peanut populations - Marubayashi, Oswaldo Massuo; Rosolem, Ciro Antonio; Nakagawa, João; Zanotto, Maurício Dutra (Pesquisa Agropecuaria Brasileira, 1997)
The objective of this work was to evaluate the response of groundnut (Arachis hypogaea L.) to different doses of phosphate fertilization (0, 40, 80 and 120 kg/ha of P2O5) for yield and quality of seeds. Triple-superphosphate (45% of P2O5 and 15% of CaO) was used. The groundnut genotypes were: Tatu, Oirã, Tupã, FCA 170 and FCA 265. The dose of 40 kg/ha of P2O5 exerced positive influence on yield and quality of seeds. The genotypes showed similar behaviour as for seed production and germination for all doses of phosphorus with interaction between genotypes and P doses as for 100 seeds weight and seed vigor. The dose of 40 kg/ha of P2O5 is enough for good production and quality of groundnut.